1996
DOI: 10.1103/physrevlett.77.651
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Stellarator Configuration

Abstract: A novel ultralow aspect ratio stellarator system that can be called a spherical stellarator (SS), in analogy with the spherical tokamak concept, is considered. The coil configuration of a simplest SS differs from that of a spherical tokamak by inclination of the external parts of the toroidal field coils. This system possesses many attractive properties including compact design and coil simplicity, good access to the plasma, closed vacuum flux surfaces with large enclosed volume, significant external rotationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 9 publications
(5 reference statements)
0
32
1
Order By: Relevance
“…As was discussed in [3][4][5][6], the SS devices benefit from the plasma current: the rotational transform increases, higher β values can be reached, and the magnetic-field ripple can be reduced substantially; also, as was stressed there, a SS can benefit not only from the ohmic current but from the bootstrap current as well, which flows in a SS in such a direction that its rotational transform enhances the vacuum rotational transform. The LARS considered with planar coils benefit from the plasma current in a similar way (section 6).…”
Section: Coil System Accommodating the Central Transformermentioning
confidence: 93%
See 4 more Smart Citations
“…As was discussed in [3][4][5][6], the SS devices benefit from the plasma current: the rotational transform increases, higher β values can be reached, and the magnetic-field ripple can be reduced substantially; also, as was stressed there, a SS can benefit not only from the ohmic current but from the bootstrap current as well, which flows in a SS in such a direction that its rotational transform enhances the vacuum rotational transform. The LARS considered with planar coils benefit from the plasma current in a similar way (section 6).…”
Section: Coil System Accommodating the Central Transformermentioning
confidence: 93%
“…One of the main new ideas behind the Spherical Stellarator concept [3][4][5][6] is that the plasma current is an important factor for improving many characteristics of such devices. In this paper it has been shown that LARS devices with planar coils benefit from the plasma current as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations